Performing in diverse settings: A diversity, equity, and inclusion approach to culture. (December 2022) - Feitosa, Jennifer; Hagenbuch, Spencer; Patel, Bansi; Davis, Alicia
Diversity, equity, and inclusion (DEI) are being built into the fabric of today's organizations, and utilizing such a lens is vital to understanding cross-cultural performance. Yet, most of the culture and diversity literature has grown in silos and is therefore not leveraging the many benefits that their integration could provide. To counter this gap, we advance a theoretical framework featuring a new definition of cross-cultural performance (CCP) from a DEI perspective, as a new angle for doing work across cultures. Specifically, CCP is defined as the integration of multiple cultural perspectives of individuals who work together with the goal of enabling a diverse, inclusive, and equitable work environment . By applying the DEI lens to CCP, we elevate the meaning of performance due to added consideration of compositional differences, the possible barriers to employees' success, and the extent to which others' perspectives are indeed valued. Accordingly, our framework identifies three main components of CCP: catalyzing cultural differences, taking part in engaging communication, and promoting allyship activities. Furthermore, we specify emotional management as the glue of these three components, and key outcomes at different levels of analysis. Last, we discuss the implications of our framework to both theory and practice as well as directions for future research.